Consistent off-shell tree string amplitudes - Liccardo, A; Pezzella, F; Marotta, R (1999)
We construct off-shell tree bosonic string amplitudes, based on the operatorial formalism of the N-string vertex, with three external massless states both for open and closed strings by requiring them to be projective invariant. In particular our prescription leads, in the low-energy limit, to the three-gluon amplitude in the usual covariant gauge.